Aplikasi Pestisida Organik untuk Pengendalian Hama Spodoptera frugiperda pada Tanaman Jagung - Christina Leta Salaki; Jackson Watung (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Salaki CL, Watung J. Application of organic pesticides for pest control spodoptera frugiperda in corn plants. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020. Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera frugiperda is a polyphagous insect pest that can cause significant yield loss if not handled properly. Not many specific control technologies to control HSMS have been found. This study aims to obtain an organic pesticide formulation to control S. frugiperda. This study used 5 organic pesticide treatments (lemon grass, clove leaves and cinnamon) at concentrations of 10%, 25%, 40%, 55% and 70%) and Control. Pesticide application is carried out by three methods, namely: Insect Spray Method, Plant Spray Method and Insect Spray Method on Plants. The parameters observed included Symptoms of Damage, Percentage of Mortality and Time of Death. Larval mortality was observed at 12,24, 48 and 72 hours after application. The difference in the proportion of mortality between levels of concentration and control was tested using the Chi-Square method, while the LT50 was tested using probit analysis. The results showed that for the insect spray method of 5 treatments the concentration of Citronella could cause 13.3-67.7% mortality, 6.7-50.0% plant spray method, insect spray method on plants 23.3-86.7 % at 72 hours after application. Meanwhile, the use of clove leaves, with 36.7-76.7% Insect Spray Method, 16.7-56.7% Plant Spray Method, 50.0-93.3% Insect Spray Method on Plants. Whereas in the use of Cinnamon, the Insect Spray Method 33.3- * 6.7%, the Plant Spray Method 20.0-60.0% and the Insect Spray Method on Plants 46.7-100% at 72 hours after application. Time of death (LT50) at a concentration of 70% treatment with the insect spray method on plants within 12 hours after application and the longest at a concentration of 10% by the plant spray method.